Tvorba materiálů pro podporu přírodovědného vzdělávání u dětí předškolního a mladšího školního věku - Andrlová, Dominika (Univerzita Karlova, Přírodovědecká fakulta, 2018)
The diploma thesis is focused on the development of natural science literacy of pre-school age children and pupils of younger school age. The aim of this thesis is didactic processing of materials which will enable teachers/lecturers/parents to develop natural science literacy of children, without themselves having to have education in chemistry for correct understanding of the experiment, and thanks to which, at the same time, they could pass on the correct information to children in such way that prevents from the occurrence of natural science misconceptions to a maximum possible extent. The theoretical part of the thesis is devoted to child ontogenesis in pre-school and early school age, which is subsequently reflected in the creation of materials for development of natural science literacy of this target age category of children. The theoretical work includes also the characterisation of the term natural science literacy as a possible tool for increasing interest in the study of natural sciences. It states the expected positives, but also possible negatives, especially in the form of resulting misconceptions which can be associated to the introduction of natural science education for younger children. In the subsequent part, an analysis of syllabus of natural science-focused subjects at. Diplomová práce je zaměřena na rozvoj přírodovědné gramotnosti dětí předškolního a žáků mladšího školního věku. Cílem této práce je didaktické zpracování materiálů, které učitelům/lektorům/rodičům umožní rozvíjet přírodovědnou gramotnost dětí, aniž by sami museli mít chemické vzdělání pro správné pochopení experimentu, a mohli zároveň předat správné informace dětem tak, aby bylo v co největší míře zabráněno vzniku přírodovědných miskoncepcí. Teoretická část práce je věnována ontogenezi dítěte v předškolním a raném školním věku, která je následně zohledněna při tvorbě materiálů pro rozvoj přírodovědné gramotnosti této cílové věkové kategorie dětí. Součástí teoretické práce je také charakteristika pojmu přírodovědná ...